2017
DOI: 10.1111/iju.13321
|View full text |Cite
|
Sign up to set email alerts
|

Daily salt intake is an independent risk factor for pollakiuria and nocturia

Abstract: Excessive daily salt intake negatively affects pollakiuria and nocturia. The presence of hypertension can also represent a worsening factor for these symptoms. Although not shown by prospective study, the appropriate control of salt intake and blood pressure might be important for the treatment of pollakiuria and nocturia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 31 publications
1
48
2
Order By: Relevance
“…In addtion, excessive salt intake is reported to be one of the most crucial determinants for Mets and lifestyle‐related diseases . Although excessive salt intake may affect the occurrence of nocturia, there is no general agreement on the relationship between salt intake and nocturia …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addtion, excessive salt intake is reported to be one of the most crucial determinants for Mets and lifestyle‐related diseases . Although excessive salt intake may affect the occurrence of nocturia, there is no general agreement on the relationship between salt intake and nocturia …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Although excessive salt intake may affect the occurrence of nocturia, there is no general agreement on the relationship between salt intake and nocturia. [14][15][16] Unfortunately, these studies have a cross-sectional design, and there is a need for prospective studies to clarify the clinical roles of salt intake. In this prospective study, we aimed to investigate whether reduced salt intake can affect LUTS, including nocturia and to determine whether salt intake reduction could be a new treatment option for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, many of the patients might have opted to consume vegetables to control their hyperglycemia. Fifth, in a previous study, the intake of salt and water affected nocturia 31,32 , but we could not estimate the intake of salt and water in the present study. Nocturia is likely a multifactorial disorder, and we could not rule out residual confounding factors.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, Kamperis et al reported that nocturnal polyuria in children with nocturnal enuresis resistant to ddavp treatment resulted from augmented sodium and urea excretion. Furthermore, a study conducted in adults also showed that excessive daily salt intake resulted in a high risk of increased daytime urination as well as nocturia . Together, these findings suggest that salt intake may affect ddavp therapy.…”
Section: Introductionmentioning
confidence: 88%